"Socialist" Factors in the US Presidential Election. Issue 3 (2nd July 2016) - Xinning, Zhang; Shaohua, Pei
ABSTRACT: Bernie Sanders, who claims to be a "socialist, " surprisingly rises from the 2016 US Democratic presidential primaries, and has created a socialist vision for future America. The "socialism" he has self-claimed for is virtually democratic socialism. Sander's meteoric rise in the election polls indicates that capitalist crisis is increasingly exacerbated; meanwhile, socialist thought tends to revitalize in the United States and other capitalist countries. The "socialism" Sanders has claimed will not take place in the United States, yet the historical tendency that socialism will inevitably replace capitalism is not going to change.